2001
DOI: 10.4065/76.10.1021
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, Diagnosis, and Treatment of Alcoholic Liver Disease

Abstract: Alcohol-related liver disease is a major cause of morbidity and mortality in the United States. Alcoholic liver disease encompasses a clinicohistological spectrum, including fatty liver, alcoholic hepatitis, and alcoholic cirrhosis. Fatty liver is a benign and reversible condition, but progression to alcoholic hepatitis and cirrhosis is life-threatening. Alcoholic hepatitis is diagnosed predominantly on clinical history, physical examination, and laboratory testing, although liver biopsy is often necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 71 publications
0
84
1
Order By: Relevance
“…This mechanistic focus in the lung contrasts the intense study of the effects of EtOH on metabolic homeostatic processes in other organs, such as the liver. It has been shown that EtOH induces significant metabolic disturbances in the liver, and these perturbations are thought to contribute to the pathogenesis of EtOHrelated liver diseases, such as alcoholic fatty liver disease, steatohepatitis, and cirrhosis (12)(13)(14).…”
Section: Clinical Relevancementioning
confidence: 99%
“…This mechanistic focus in the lung contrasts the intense study of the effects of EtOH on metabolic homeostatic processes in other organs, such as the liver. It has been shown that EtOH induces significant metabolic disturbances in the liver, and these perturbations are thought to contribute to the pathogenesis of EtOHrelated liver diseases, such as alcoholic fatty liver disease, steatohepatitis, and cirrhosis (12)(13)(14).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Both diseases encompass a spectrum of histopathology, ranging from steatosis to cirrhosis. 4,5 Steatohepatitis is believed to be an intermediate stage in the progression from steatosis to cirrhosis, because the probability of developing advanced hepatic fibrosis is significantly greater in individuals with steatohepatitis than in those with simple steatosis. 4,6,7 Efforts have focused on delineating the pathogenesis of steatohepatitis so that effective treatments to interrupt progression from relatively occult to clinically significant liver disease might be developed.…”
Section: A Lthough Nonalcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…In addition, a large body of literature indicates the role of alcohol metabolites, reactive oxygen/ nitrogen species (RNS/ROS), bacterial translocation from the gut, TNF-α and hepatic stellate cell (HSC) activation as the combined cause of alcohol-induced hepatic damage. Therefore, a consensus has been emerging concerning the general pathway culminating in severe ALD involving a complex orchestration between Kupffer cells (KCs), HSC and hepatocytes (7,9,16). This study reviews these concepts and highlights the key role played by the noradrenergic stimuli NE and its receptor in the causation of alcohol-derived injury in the liver.…”
Section: … If the Surfeit Of Delicacies Or The Hereditary Wine Of Mymentioning
confidence: 99%
“…Alcohol, however, has also beneficial effects, and moderate alcohol consumption has been shown to improve digestion and cholesterol profile, and to lower the risk of ischemic heart disease (12,13). Epidemiological data has shown a clear correlation between excessive and prolonged alcohol consumption and liver disease (6,7). The molecular mechanisms underlying these interactions are still being elucidated.…”
Section: … If the Surfeit Of Delicacies Or The Hereditary Wine Of Mymentioning
confidence: 99%
See 1 more Smart Citation